National Health Policy Reform for Primary Care in Chile: A Qualitative Analysis of the Health Program Documents - Karen A. Dominguez-Cancino; Patrick A. Palmieri; Maria Soledad Martinez-Gutierrez (SAGE Publishing, 2020)
Introduction: Chilean policy makers reformed the national health policy for primary health care (PHC), shifting from the traditional biomedical model to the integral family and community health model with a biopsychosocial approach, to guide the delivery of PHC throughout the country. Purpose: To evaluate the implementation of the national health policy for PHC through an analysis of the program documents for PHC; and to identify to what extent the national health policy is expressed in each program document, and across all the documents. Methods: A qualitative document analysis with a purposive sample of program documents for PHC. The Chilean Ministry of Health website was systematically searched between October and December 2018 to identify relevant program documents. Thematic and content analysis were performed to identify evidence of the biopsychosocial approach to care delivery with each program document, including the types of interactions between professionals that contribute to person-centered or fragmented care. Results: The study included 13 PHC program documents. Three themes and 10 categories emerged from the data. Most program justifications focused on the biopsychosocial approach to care while including biomedical interventions and supporting independent professional work. Only 4 of the 13 programs were consistent in the justification, interventions, and types of stated professional interactions: 2 from the biopsychosocial and 2 from the biomedical perspectives. Conclusion: In terms of the national health policy for PHC in Chile, interprofessional collaboration and person-centered care processes and practices were partially aligned with the written content of the health program documents. As such, policy makers and health sector leaders are advised to analyze draft health program documents for consistency in translating national health policies into the written communications that define the actualization of the care model in PHC and direct professionals how to provide PHC to individuals and families.